Features of advertising perception by children - Skryhun, Natalya; Solomonenko, Viktoria (My University, 2013)
The advertising perception by children is reviewed. It is described the impact of advertising on children's behavior and reaction. It is defined the methods of influence of advertising on children. Розглянуто особливості сприйняття реклами дітьми.
Keywords: advertising; advertising perception; methods of influence of advertising; advertising techniques; реклама; сприйняття реклами; методи впливу реклами; рекламні прийоми; реклама; восприятие рекламы; методы воздействия рекламы; рекламные приемы; кафедра маркетингу